Role of lactation educators in urban India: A comparative study - Rajadhyax, Mamata; Jaju, Neeta Saboo; Pawaskar, Lukmita; Mali, Satish (Indian Journal of Child Health, 2017)
Objective: To study the impact of postnatal lactation counseling by certified lactation educator on the establishment of breastfeeding in urban areas. Design: Retrospective observational study Setting: Maternity ward of a multispecialty Private Hospital in Thane City of Maharashtra. Materials and Methods: During March 2014 to February 2015, data were collected retrospectively from the hospital records of 283 mothers (study group) who had delivered healthy newborns at full term with birth weight of >2.5 kg and had received structured lactational counseling from the lactation educator. This was compared with the data from March 2013 to February 2014 when 235 mothers (control group) received lactational counseling from the maternity staff after delivery. Main Outcome Measures: Reduction in the volume of supplemental formula feed during the hospital stay and number of babies discharged on exclusive breastfeeding (i.e., no supplemental formula feed given in the 24 h before discharge). Results: The mean volume of supplemental formula consumed was significantly lesser (p